Strategi Pengembangan Ekonomi Keluarga Daerah Wisata melalui Pemasaran Digital di SMA Negeri 1 Sukapura Probolinggo - Sulastri Sulastri; Mita Asmira (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2025)
The increasing number of visitors in the Bromo tourism area has created significant economic opportunities for local families, yet most still lack digital marketing skills and the ability to communicate in English. The English-Based Digital Marketing Program initiated by SMA Negeri 1 Sukapura was designed as a vocational education strategy rooted in community empowerment to simultaneously strengthen students’ competencies and support family-owned businesses. This community service program applied the Asset-Based Community Development (ABCD) approach through training, hands-on practice, mentoring for digital promotion, and English communication for business transactions. The results show a substantial improvement in students’ digital literacy and English proficiency, which led to higher-quality promotional content, increased online visibility of businesses, and growth in customer reach and orders for local family enterprises. The program reinforces the role of the school as a center of social innovation and demonstrates an effective model for integrating education with community economic development in a tourism-based region.